The morphology of the right ventricular outflow tract after percutaneous pulmonary valvotomy: long term follow up. Issue 3 (September 1987) - Robertson, M; Benson, L N; Smallhorn, J S; Musewe, N; Freedom, R M; Moes, C A; Burrows, P; Johnston, A E; Burrows, F A; Rowe, R D
Abstract : Twenty nine patients (19 male, mean (SD) age 6.25 (0.5) years (range 0.16-15 years] with typical pulmonary valve stenosis were treated by balloon dilatation of the pulmonary valve. They were studied by echocardiography before the procedure, immediately after it, and at follow up (mean (SD) 10.2 (5.6) months, n = 18). The morphology of the pulmonary valve, the right ventricular-pulmonary artery gradient, and ratio of the systolic to diastolic endocardial dimensions (infundibular ratio) were examined. No patient had pulmonary regurgitation before the study. The valve gradient was significantly reduced (47%) from a mean (SD) of 72 (31) to 37 (23) mm Hg with no short term change in cardiac index after dilatation with a balloon with a mean (SD) diameter that was 118 (10.8)% of the valve annulus. The infundibular ratio was unchanged by the procedure (0.49 (0.11) (n = 21) before dilatation and 0.47 (0.14) (n = 16) after dilatation). In twenty seven patients the commissure of the pulmonary valve was seen to be torn after dilatation. Two patients with bicuspid valves had flail leaflets. Doppler examination at follow up showed mild pulmonary insufficiency in all 29 patients; the mean (SD) valve gradient (31 (+/- 21) mm Hg) at follow up was no different from the gradient found immediately after the procedure and infundibular ratio (0.58 (0.15) was not abnormal. These data indicate that commissural tears are the primary mechanism of valve disruption and demonstrate that the dynamic right ventricular outflow tract obstruction relaxes and gradient reduction persists at follow up.